Isoniazid protects mice against endotoxin lethality without influencing tumor necrosis factor synthesis and release. - Urbaschek, R (1991)
Treatment of NMRI mice with isoniazid (INH; 25 mg/kg) intraperitoneally induced significant protection when it was injected before or after a lethal intravenous challenge with endotoxin. The INH preparation used was not contaminated with endotoxin. Tumor necrosis factor (TNF) was not elevated in sera from NMRI mice 2 h after the injection of INH. INH did not influence TNF synthesis or release determined in human monocytes in vitro. Therefore, it is concluded that the protective effect of INH against lethal endotoxin is not due to a suppressive effect of INH on TNF production.